Relationship Between Nutritional Status and Fine Motor Skill Development of Class B PAUD Students in Kediri District, West Lombok - Nina Anggraini; Kusmiyati Kusmiyati; Dewa Ayu Citra Rasmi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This original research paper employs a quantitative cross-sectional analytic design to investigate early childhood development in a specific Indonesian setting. This study aimed to analyze the relationship between nutritional status and fine motor skill development in class B preschool children (aged 5–6 years) in Kediri District, West Lombok, Indonesia. A quantitative cross-sectional analytic design was used. The sample consisted of 67 children from five PAUD selected by proportional random sampling. Nutritional status was assessed using BMI-for-age (IMT/U) based on WHO standards, while fine motor skill development was measured through structured observation using seven indicators. Data were analyzed using Chi-Square and Fisher's Exact Test. Results showed that most children had normal nutritional status (67.1%), 29.9% were undernourished, and 1.5% each were overweight and obese. Fine motor skill development was in the